Macroprudential policies in the EAGLE FLI model calibrated for Hungary - Gábor Fukker; Lóránt Kaszab (Magyar Nemzeti Bank, 2019)
In this paper we develop the Hungarian version of the EAGLE FLI (Euro Area GLobal Economy model with Financial LInkages) model which is the EAGLE model enriched with financial frictions and country-specific banking sector. The EAGLE FLI features the intermediation of loanable funds (ILF) view in banking whereby the creation of new loans requires banks to collect additional deposits. Households and firms borrow in the model using housing as collateral. We find that macroprudential policies such as an increase in capital requirements, decreases in the loan-to-value ratio or loan-to-income ratio of borrower households (and firms) limits banks' credit creation with negative spillover effects to the real economy due to the financial accelerator mechanism in the model. On the other hand, these policies strengthen banks' capital and limit the vulnerability of households and firms to negative financial shocks.
Keywords: E12; E13; E52; E58; F11; F41; 330; macroprudential policy; multi-country DSGE; capital requirements; loan-to-value ratio; loan-to-income ratio